2021
DOI: 10.1016/j.jbankfin.2020.105992
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the ECB's targeted long-term refinancing operations on banks’ lending policies: The role of competition

Abstract: This paper should not be reported as representing the views of the European Central Bank (ECB). The views expressed are those of the authors and do not necessarily reflect those of the ECB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 27 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…For instance, asset purchases by the central bank may increase asset prices, lead to a decrease in yields, and thus, make lending more attractive for banks (Kapoor & Velic, 2022). In addition, monetary policy actions such as low interest rates may encourage higher yields aiming banks to extend loans to risky firms (Andreeva & García-Posada, 2021;Jiménez et al, 2018;Jimenez et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, asset purchases by the central bank may increase asset prices, lead to a decrease in yields, and thus, make lending more attractive for banks (Kapoor & Velic, 2022). In addition, monetary policy actions such as low interest rates may encourage higher yields aiming banks to extend loans to risky firms (Andreeva & García-Posada, 2021;Jiménez et al, 2018;Jimenez et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many problems are faced by the SMEs, these include the lack of a steady power supply, lack of finance, poor technology, and others. In ensuring that the SMEs are well funded and overcome some of these difficulties, many governments use different policies, especially monetary policy to aid their operations (Andreeva, & García-Posada, 2021;European Commission, 2022;Finnegan & Kapoor, 2023). In Nigeria, the CBN reports that only 5 percent of SMEs have access to adequate finance covering their working capital and that about N617.3 billion financing gap is required for the SMEs each year.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to granting a funding cost relief, TLTROs are different from standard non-targeted operations in that they require the achievement of lending targets by participants. The higher propensity to lend for participants increases competitive pressures in lending markets, inducing also nonparticipants to ease lending criteria in order to protect their market share (Andreeva and García-Posada 2021). TLTROs also ease regulatory constraints related to liquidity requirements, and ultimately inject further central bank liquidity in the system, exerting downward pressure on the cost of interbank funding.…”
Section: Addressing Identification Challengesmentioning
confidence: 99%
“…Jiménez et al 2014) that emerged after the financial crisis and flourished during the period of low policy interest rates. More recently, this literature has also covered the effect of targeted central bank liquidity operations on banks' risktaking behaviour and found that these measures did not lead to excessive risk-taking (Andreeva and García-Posada 2021;Esposito et al 2020). These papers focus on past generations of the TLTRO series, which were conducted in a period that was not yet characterised by a prolonged low interest rate environment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the FFL requirement to disburse low-cost funds into loans to the real sectors during the economic downturn may lead banks to loosen their lending standards. The cheap liquidity is expected to bring down costs of credit so that banks can offer lower loan interest rates ( Balog et al, 2014 , Benetton and Fantino, 2018 , Andreeva and García-Posada, 2021 ). However, as credit risks rise during economic downturns, banks become more risk-averse and costs of credit tend to increase.…”
Section: Introductionmentioning
confidence: 99%